2019
DOI: 10.1262/jrd.2019-001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manganese on maturation of porcine oocytes <i>in vitro</i> and their subsequent embryo development after parthenogenetic activation and somatic cell nuclear transfer

Abstract: This study was carried out to examine the effects of manganese (Mn) on the developmental competence of porcine oocytes during in vitro maturation (IVM) after parthenogenetic activation (PA) and somatic cell nuclear transfer (SCNT). Upon treatment of porcine oocytes with different concentrations (0, 3, 6, and 12 ng/ml) of Mn during IVM, PA was performed to determine the optimum concentration. Following PA, the rate of blastocyst formation was higher significantly in treated porcine oocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…A previous study suggested that SOD1 deficiency increased superoxide generation, thereby exhibiting abnormal embryo development in murine oocytes [ 36 , 37 ]. Therefore, our results were consistent with most experiments on antioxidant supplementation, which indicated that antioxidants provided advantageous microenvironment to improve oocyte maturation by protecting oocytes against ROS in pigs [ 19 , 33 , 38 , 39 ]. Indeed, supplementation of melatonin during IVM could improve oocyte maturation and their subsequent embryo development by reducing oxidative stress and DNA damage in various species [ 40 , 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 90%
“…A previous study suggested that SOD1 deficiency increased superoxide generation, thereby exhibiting abnormal embryo development in murine oocytes [ 36 , 37 ]. Therefore, our results were consistent with most experiments on antioxidant supplementation, which indicated that antioxidants provided advantageous microenvironment to improve oocyte maturation by protecting oocytes against ROS in pigs [ 19 , 33 , 38 , 39 ]. Indeed, supplementation of melatonin during IVM could improve oocyte maturation and their subsequent embryo development by reducing oxidative stress and DNA damage in various species [ 40 , 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 90%
“…The effect of enrichment on the follicular environment can be two-sided. Mn was found to be beneficial to the development of oocytes, , and the Ni 2+ binding protein pNiXa can induce oocyte maturation in Xenopus . These enrichment phenomena suggest the special demands of the metal balance during oocyte development.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no substantial difference in the cleavage rate and total cell numbers in blastocysts compared to the untreated group. Manganese improved the developmental competence of cloned porcine embryos by increasing GSH and decreasing ROS levels [232].…”
Section: Alternative Methods For Cloning Efficiency Improvementmentioning
confidence: 98%